Avaliação da possibilidade de erosão natural e induzida na bacia hidrográfica do ribeirão das pedras, Quirinópolis (GO) - Rodrigues, Flávio Henrique [UNESP]; Coelho, Juliano Martins [UNESP]; dos Santos, Fátima Sueli Marcon [UNESP]; do Amaral, Ana Maria Carrascosa [UNESP]; Zaine, José Eduardo [UNESP] (My University, 2014)
This paper presents the results of a study of rating susceptibility to erosion in the Ribeirao das Pedras basin, city of Quirinopolis - Goiás state. The procedures were based on analysis of aerial photography and satellite images, field survey, geological and geomorphological zonation, and evaluation of natural and induced erosion process. A framework matrix was applied for estimate the susceptibility to the occurrence of natural and induced erosion. The main result consist in a Map of Erosion Susceptibility, that evaluates the susceptibility of the terrain to natural erosion, as well were pointed critical sectors of high possibility of induced and/or accelerated erosion. Terrains with weathering sandstone in the plateau top, and those with problems arising from urbanization and agricultural activity are pointed as the most susceptible to natural and induced erosion respectively.
Assessing the possibility of natural and induced erosion in the watershed of the Ribeirao das Pedras, Quirinopolis (GO)
Keywords: Erosion susceptibility; Physiographic analysis; Quirinopolis (Goias, Brazil)